The History of TIRDO and Industrialization in Tanzania up to 2018 - Kapinga, Osmund; Gores, Victoria (Machakos University Press, 2019)
This paper examines different areas which are the prerequisites of industrialization. It focuses on the issues of research and innovation as imperatives in industrialization from historical point of view, the paper utilizes the case study of Tanzania Industrial Research and Development (TIRDO) as a research institution established for the purpose of advancing industrialization in Tanzania. The paper focuses on the circumstances which prompted the establishment of the institution and the purpose for which it was established. The functions and roles of the institution have been reviewed and dissected from the historical point of view. The successes, challenges and future prospects have been discussed in line with industrialization. Methodologically the paper has been designed from historical exploratory design utilizing a case study strategy. The approach engaged in this paper is that of qualitative nature utilizing both primary and secondary historical sources to gather information through in depth interviews, oral histories, observation and intensive archival documentary review. Research instruments such as interview guides and checklists were designed to facilitate smooth collection of the required data. Most of the secondary data were generated from libraries at SAUT, MWECAU, UDSM, National Library DSM, Mwanza Regional Library and Kilimanjaro Regional Library. The findings revealed that TIRDO was created with very strong ambitions to advance industrialization in Tanzania. However, the functions of which were marred by lack of commitment and unnecessary bureaucratic bottlenecks. Budgetary problems and structural organizational inconsistencies crumbled the smooth functioning of the institution.
Keywords: Industrialization; Innovation; TIRDO; Research; Local industries